Claw morphometrics in monitor lizards: Variable substrate and habitat use correlate to shape diversity within a predator guild. Issue 13 (11th June 2018) - D'Amore, Domenic C.; Clulow, Simon; Doody, J. Sean; Rhind, David; McHenry, Colin R.
Abstract: Numerous studies investigate morphology in the context of habitat, and lizards have received particular attention. Substrate usage is often reflected in the morphology of characters associated with locomotion, and, as a result, claws have become well‐studied ecomorphological traits linking the two. The Kimberley predator guild of Western Australia consists of 10 sympatric varanid species. The purpose of this study was to quantify claw size and shape in the guild using geometric morphometrics, and determine whether these features correlated with substrate use and habitat. Each species was assigned a Habitat/substrate group based on the substrate their claws interact with in their respective habitat. Claw morphometrics were derived for both wild caught and preserved specimens from museum collections, using a 2D semilandmark analysis. Claw shape significantly separated based on Habitat/substrate group. Varanus gouldii and Varanus panoptes claws were associated with sprinting and extensive digging. Varanus mertensi claws were for shallow excavation. The remaining species' claws reflected specialization for some form of climbing, and differed based on substrate compliance. Varanus glauerti was best adapted for climbing rough sandstone, whereas Varanus scalaris and Varanus tristis had claws ideal for puncturing wood. Phylogenetic signal also significantly influenced claw shape, with Habitat/substrate group limited to certain clades. Positive size allometry allowed for claws to cope with mass increases, and shape allometry reflected a potential size limit on climbing. Claw morphology may facilitate niche separation within this trophic guild, especially when considered with body size. As these varanids are generalist predators, morphological traits associated with locomotion may be more reliable candidates for detecting niche partitioning than those associated directly with diet. Abstract : We quantified the claw morphology of sympatric monitor lizards found in the Kimberley of Western Australia through a geometric morphometric analysis. There was significant claw shape and size variability correlating to the biomechanical limitations of the substrate the lizards interacted with, as well as phylogeny and allometry. Claw morphology therefore likely facilitates niche partitioning in this guild.